(untitled) (Global Journal of Human-Social Science, 2022)
The expansion of sugarcane crop in watersheds, located in the regions of Marilia and Presidente Prudente, in the interior of São Paulo, by replacing degraded pastures, is altering soil cover and influencing erosive processes. This article aims to analyze the land cover changes in the basin of Confusion’s stream and relate to the parameters of the factors of the Universal Soil Loss Equation. The land cover charts were generated with images of CBERS’s satellite dated 2009 and 2018 by supervised classification. The areas of the land cover classes were related to factor C of the USLE and data estimates of secondary sources of erosivity factor (R), erodibility factor (K) and topographic factor with the data of slope (LS). From these parameters, an estimate of soil loss was presented for the basin of Confusion’s stream. The soil loss in the basin of Confusion’s stream was estimated by 2018 data at 2,484 t/ha/y.